Measuring Teachers' Awareness of the Quality Standards of Educational Effectiveness in Secondary Schools - a Case Study (The International Journal of Educational Sciences and Arts, 2023)
Quality standards in secondary education represent the most important controls that govern the teacher’s performance and help him evaluate it. The effectiveness of his performance depends on it, and the effectiveness of the entire educational process depends on it. Despite the interest of education officials in Jordan to define national standards for secondary education, there is still a lack of awareness. These standards by secondary school teachers, and this low awareness would negatively affect the outputs of that stage and impede the achievement of its desired goals - and then this was the study that tried to reveal the reality of the awareness of secondary education teachers in Jordan about the quality standards of educational effectiveness in their schools, which can Have a positive impact on improving their school performance.The study used the descriptive approach, which relies on collecting and classifying data and information to identify the awareness of secondary education teachers in Jordan of the quality standards of educational effectiveness in their schools. A questionnaire was designed and applied to a sample of secondary teachers in Jordan to identify their awareness of these standards. The study was applied to a sample of secondary education teachers in Zarqa, in the academic year 2020/2021.
Keywords: Teachers' Awareness; Quality Standards; Educational Effectiveness; Secondary Schools